2023
DOI: 10.1002/adfm.202311664
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Shell Dependent Activity of CuCo Diatomic Catalysts for Oxygen Reduction, Oxygen Evolution, and Hydrogen Evolution Reaction

Yuqing Chen,
Jianing Mao,
Hu Zhou
et al.

Abstract: Challenges in rational designing dual‐atom catalysts (DACs) give a strong motivation to construct coordination‐activity correlations. Here, thorough coordination‐activity correlations of DACs based on how the changes in coordination shells (CSs) of dual‐atom Cu,Co centers influence their electrocatalytic activity in oxygen reduction reaction(ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) is constructed. First, Cu,Co DACs with different CSs modifications are fabricated by using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…Given this extremely low level of Fe, it is evident that such a trace amount is insufficient to contribute to the catalytic properties of the fabricated carbocatalysts. Of note, methanol tolerance is also an important performance parameter in the electrocatalytic ORR process, which is crucial for the use of electrodes in fuel cells . GDHfCN electrode exhibits almost no change in current density upon the addition of 0.5 M methanol solution (Figure S11), whereas the commercial Pt/C electrode exhibits a significant decay in current density, implying the potential advantage of GDHfCN as an ORR cathode catalyst in practical fuel cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given this extremely low level of Fe, it is evident that such a trace amount is insufficient to contribute to the catalytic properties of the fabricated carbocatalysts. Of note, methanol tolerance is also an important performance parameter in the electrocatalytic ORR process, which is crucial for the use of electrodes in fuel cells . GDHfCN electrode exhibits almost no change in current density upon the addition of 0.5 M methanol solution (Figure S11), whereas the commercial Pt/C electrode exhibits a significant decay in current density, implying the potential advantage of GDHfCN as an ORR cathode catalyst in practical fuel cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al found that FeCoN 7 and FeCoN 8 possess better catalytic activity and stability compared with FeCoN 6 both for ORR and OER . Chen et al found that the initial modifications in the first nearest neighbor coordination for CuCo DACs may not always be advantageous for electrocatalysis in OER . Even though DACs have made great achievements as electrocatalysts in the OER, the role of the local coordination environment of the active sites in enhancing the OER activity has not yet been fully understood, especially the regulation of the OER catalytic performance by the second nearest neighbor coordination of the active sites in atomically dispersed metal catalysts.…”
Section: Introductionmentioning
confidence: 99%